Book Review of Alison Phipps’ Me, Not You: The Trouble with Mainstream Feminism - Berraf, Hana Lina Dalel (AMERICANA E-journal of American Studies in Hungary, 2022)
Me, Not You: The Trouble with Mainstream Feminism Alison Phipps Manchester: Manchester University Press, 2020 205 pages ISBN 978 1 5261 4717 2